(untitled) (Journal of Education and Academic Settings, 2026)
This study explored how the Induction Program for Beginning Teachers (IPBT) was implemented in the Schools Division of Calbayog City, with particular focus on the engagement of public elementary school teachers and the challenges experienced during the program’s implementation. Recognizing the importance of helping novice teachers adjust to the teaching profession, the study sought to evaluate the extent of IPBT implementation, assess teachers’ level of engagement, and identify the common issues encountered across selected districts. The study used a quantitative approach through a descriptive–correlational–comparative research design. A total of 100 beginning teachers from the Tinambacan and Oquendo Districts participated in the study and were selected using stratified random sampling. Data were gathered through a validated researcher-made questionnaire and analyzed using frequency counts, percentages, weighted mean, and non-parametric statistical tools, including the Mann–Whitney U test and Kruskal–Wallis H test. The findings showed that the major components of the IPBT such as program orientation, mentoring, supervision, and coursebook utilization were generally perceived as consistently implemented. The respondents also exhibited a strong level of engagement in terms of affective, behavioral, and cognitive dimensions. Despite these positive results, participants reported several challenges, particularly concerning communication, availability of resources, mentoring support, and monitoring processes. The study further revealed that although the IPBT is generally well-structured and effectively implemented, its overall success is still affected by contextual factors such as resource availability, administrative support, and consistency in program delivery. These findings highlight the need to strengthen support systems, improve mentoring practices, and address operational concerns to further enhance the effectiveness of the program. Ultimately, the study provides a basis for developing a localized innovation aimed at improving the implementation of the IPBT and supporting the professional growth and development of beginning teachers.